Study about Classified Indian Reclaimed Asphalt Pavement (RAP): In-situ and Lab Density, Bitumen Content and Gradation Characteristics - Anil Kumar Yadava; Syed Aqeel Ahmad (Current Overview on Science and Technology Research Vol. 7, 2022)
In this study, bitumen content, in-situ and lab density, and gradation of RAP divided into various categories were used to characterise RAP. The findings of this study will be helpful in designing the job mix formula (JMF), which will incorporate RAP in variable percentages in the bituminous layer of flexible pavements. This study is a step toward environmentally friendly developments that combine flexible pavement construction with resource conservation and environmental protection. Asphalt and aggregate-containing pavement materials that have been removed and/or reprocessed are referred to as reclaimed asphalt pavement (RAP). When asphalt pavements are removed for reconstruction, resurfacing, or to get access to underground services, these materials are produced. RAP is made up of high-quality, well-graded aggregates covered in asphalt cement after being carefully crushed and screened. Recycling of asphalt pavement refers to the process of using reclaimed asphalt pavement (RAP). When old, damaged pavement materials are milled and crushed to be included as a component to fresh mixtures installed in the pavement construction, RAP material is produced. The central plant process involves stockpiling RAP at the asphalt plant, which is then mixed with virgin materials at the plant and trucked to the construction site for lay down and compaction. Use of RAP in road construction will reduce depletion of virgin aggregates resources and also overcome to disposal problem of bituminous wastes. It is required to access properties of RAP aggregate and recovered bitumen before using in actual road pavements. RAP samples collected and a series of tests are performed for characterization and performance evaluation of selected RAP samples of different groups.